"Delay to operating room" fails to identify adverse outcomes at a Level I trauma center. Issue 2 (February 2017) - Lewis, Paul R.; Badiee, Jayraan; Sise, Michael J.; Calvo, Richard Y.; Brill, Jason B.; Wallace, James D.; Shackford, Steven R.; Dunne, Casey E.; Bansal, Vishal; Sise, C. Beth
Abstract : BACKGROUND: The American College of Surgeons Committee on Trauma devised process audit filters to identify opportunities for improvement (OFI), prevent adverse outcomes, and improve quality. Delay to the operating room for primary trauma laparotomy is a process audit filter that has not been definitively associated with improved outcomes. We sought to evaluate the effectiveness of delay to the operating room of greater than 2 hours (DOR) to independently identify an adverse outcome or an OFI at our Level I trauma center. METHODS: Trauma patients who underwent primary exploratory laparotomy from July 2006 to March 2015 were reviewed. Those with DOR were identified and compared with those without DOR. To analyze the ability of DOR to independently identify an adverse outcome or an OFI, DOR patients were further divided into those with isolated DOR and those with DOR in conjunction with one or more other process audit filter. Primary outcome was the presence of a complication. Secondary outcome was an identified OFI. Medical records of patients with either outcome were reviewed to determine if the outcome resulted directly from DOR. RESULTS: Of 472 patients, 109 (23%) had DOR and 363 (77%) did not. There were no significant differences in age, sex, or injury severity between the two groups. The rates of complications among DOR patients and those without DOR were not significantly different (35% vs. 38%, p = 0.59). The DOR was the only process audit filter flagged in 31(28%) patients in the DOR group. This subgroup had no identified complications but incurred two OFIs; neither OFI was associated with an adverse outcome. CONCLUSION: In trauma patients undergoing primary exploratory laparotomy, DOR fails to independently identify adverse outcomes. These findings suggest that DOR, as a routinely collected process audit filter, is not an effective indicator of suboptimal care or adverse outcomes at a Level I trauma center. LEVEL OF EVIDENCE: Therapeutic study, level IV; prognostic study, level III.